The ETI-dependent receptor-like kinase 1 positively regulates effector-triggered immunity by stabilizing NLR-required for cell death 4 in Nicotiana benthamiana - Sun, Yujing (The New phytologist, 2024)
© 2024 The Authors New Phytologist © 2024 New Phytologist Foundation.